An Adult Developmental Approach to Perceived Facial Attractiveness and Distinctiveness - Ebner, Natalie C.; Luedicke, Joerg; Voelkle, Manuel C.; Riediger, Michaela; Lin, Tian; Lindenberger, Ulman (Frontiers in Psychology, 2018)
Attractiveness and distinctiveness constitute facial features with high biological and social relevance. Bringing a developmental perspective to research on social-cognitive face perception, we used a large set of faces taken from the FACES Lifespan Database to examine effects of face and perceiver characteristics on subjective evaluations of attractiveness and distinctiveness in young (20–31 years), middle-aged (44–55 years), and older (70–81 years) men and women. We report novel findings supporting variations by face and perceiver age, in interaction with gender and emotion: Although older and middle-aged compared to young perceivers generally rated faces of all ages as more attractive, young perceivers gave relatively higher attractiveness ratings to young compared to middle-aged and older faces. Controlling for variations in attractiveness, older compared to young faces were viewed as more distinctive by young and middle-aged perceivers. Age affected attractiveness more negatively for female than male faces. Furthermore, happy faces were rated as most attractive, while disgusted faces were rated as least attractive, particularly so in middle-aged and older perceivers and in young and female faces. Perceivers largely agreed on distinctiveness ratings for neutral and happy emotions, but older and middle-aged compared to young perceivers rated faces displaying negative emotions as more distinctive. These findings underscore the importance of a lifespan perspective on perception of facial characteristics and suggest possible effects of age on goal-directed perception, social motivation, and in-group bias. This publication makes available picture-specific normative data for experimental stimulus selection.